2023
DOI: 10.1126/science.adf8822
|View full text |Cite
|
Sign up to set email alerts
|

Control of histone demethylation by nuclear-localized α-ketoglutarate dehydrogenase

Abstract: Methylations on nucleosomal histones play fundamental roles in regulating eukaryotic transcription. Jumonji C domain–containing histone demethylases (JMJs) dynamically control the level of histone methylations. However, how JMJ activity is generally regulated is unknown. We found that the tricarboxylic acid cycle–associated enzyme α-ketoglutarate (α-KG) dehydrogenase (KGDH) entered the nucleus, where it interacted with various JMJs to regulate α-KG–dependent histone demethylations by JMJs, and thus controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The distribution of metabolites is highly heterogeneous within cells (Li et al, 2023 ). Metabolic enzymes have been demonstrated to alter metabolite levels and efficiently modulate the activity of their interacting proteins (Huang et al, 2023 ; Wang et al, 2019 ). To identify potential targets of SUCLG1, we assayed the interaction between SUCLG1 and regulators of mtDNA replication and transcription.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of metabolites is highly heterogeneous within cells (Li et al, 2023 ). Metabolic enzymes have been demonstrated to alter metabolite levels and efficiently modulate the activity of their interacting proteins (Huang et al, 2023 ; Wang et al, 2019 ). To identify potential targets of SUCLG1, we assayed the interaction between SUCLG1 and regulators of mtDNA replication and transcription.…”
Section: Resultsmentioning
confidence: 99%
“…LSD1 catalyzes the demethylation of mono- or dimethylated H3K4 and H3K9, whereas LSDs act as receptors in the mitochondrial ETC ( 161 ). JMJD-mediated demethylation of histones requires α-ketoglutarate ( 162 ), a substrate produced mainly by the tricarboxylic acid (TCA) cycle in the mitochondrial matrix. Current research has found that low methylation of DNMT1/DNMT3a/DNMT3b/DNMT3L promotes oocyte aging ( 17 ).…”
Section: Mitochondrial Dysfunction Leads To Ovarian Agingmentioning
confidence: 99%
“…On the other hand, in oligodendrocytes and their precursors, hGDH1 is expressed in the cell nucleus [46,47]. While this nuclear localization may appear aberrant, α-ketoglutarate dehydrogenase, another metabolic enzyme of the TCA cycle linked to GDH function, can also localize to the cell nucleus, where it generates α-ketoglutarate needed for gene regulation via histone modification [74]. Whether hGDH1 serves a similar function in dividing glial cells needs to be further understood.…”
Section: Studies On Human Central Nervous Tissuementioning
confidence: 99%